Kampung Wisata Berbasis Masjid di Kampung Sayidan Prawirodirjan Yogyakarta - Ahmad Kharis (Islamic Management and Empowerment Journal, 2019)
This article aimed to describe the organizing process to empower village communities through mosque-based tourism in Sayidan Village. This research was a descriptive qualitative research which aimed to explain the process of organizing village tours through mosques. The procedure of this study resulted in descriptive data consisting of written words, oral words of the people who were received. Snowball techniques were used to collect data, interviews, observation and documentation. The results in this study were the Sayidan Tourism Village which originated from the assumption that people in the community needed to be restless because the river sometimes caused flooding. But the community was able to turn disaster into a blessing through Tourism Village. More than the mosque basecamp was delivered during a scussion meeting which led to the idea of a tourist village. When the process of organizing the community makes Mosque-Based Tourism Village among others, a. Emergence of Ideas: Discovery (Discovery) to Dreams (Dreams), b. Planning (Design): Detailing not what was needed, c. Defining (Defining): Raising mutual strength, d. Implement (Destiny): Ensure the plan has been implemented